The effect of fenofibrate, a peroxisome proliferator-activated receptor α agonist, on cardiac damage from sepsis in BALB/c mice - Lv, Mingyi; Xie, Dengmei; Long, Xiaofeng (Cellular and Molecular Biology, 2022)
Cardiac dysfunction can be a fatal consequence of sepsis and lead to increased inflammatory responses or reduced fatty acid oxidation and final ATP depletion. Fenofibrate, which is an agonist of peroxisome proliferator-activated receptor α, has been used primarily in hypercholesterolemia and mixed dyslipidemia. Recent studies found that fenofibrate could alleviate energy metabolism and inflammation caused by cardiac damage during sepsis, and thus it had been paid great attention. This study was to investigate the possible protective roles of fenofibrate against cardiac damage in septic BALB/c mice. Methods: Forty male BALB/c mice aged 8 weeks old were divided randomly into four groups: control group; fenofibrate group; cecal ligation and puncture (CLP) group; and fenofibrate + CLP group. After administering fenofibrate or saline for 2 weeks, CLP was performed. Cardiac tissue and plasma were obtained 48 hours later. Plasma Troponin-T (Tnt), ATP, ADP and reactive oxygen species (ROS) levels were determined. PPARα and 53 protein levels were detected using western blotting. IL-6 and tumor necrosis factor-α (TNFα) were also assayed. We found that fenofibrate decreased plasma cTnT, ROS and increased the ratio of ATP/ADP. The elevations of IL-6, TNFα and P53 induced by sepsis were significantly suppressed by fenofibrate. Our results suggest that fenofibrate can regulate energy metabolism efficiently, which makes it a possible agent for treating sepsis-induced cardiac damage.